Hijab Discourse in Indonesia: The Battle of Meaning Between Sharia and Culture in Public Space - Zain, Muhammad; Aaisyah, Sitti; Alimuddin, Asriaty; Abdillah, Akhmad Mughzi; Fauzi, Muhammad Fahmi Basyhah (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
The phenomenon of wearing hijab is not only a reality in Indonesia but also in the Muslim world and even the world in general such as Europe, America, and Australia. This paper aims to examine the discourse on hijab between Islamic law (sharia) and culture. This is a normative study using legal pluralism as an approach.  This paper concludes that Indonesia has the largest Muslim population in the world, and the wearing of hijab has a long history until contemporary times. Currently, the phenomenon of hijra among Muslims is also on the rise, the hijab is then formalized into educational institutions and offices which not a few cause problems that sometimes arise discriminatory actions to those who do not want to use it. Another phenomenon about the use of hijab occurs in the realm of law. A woman dealing with legal issues, when presented at a press conference, some public figures wear hijab. Even in the judicial room, women who usually do not wear headscarves also change their appearance by wearing headscarves. Likewise, in a political campaign, women who usually do not wear headscarves, appear in hijab suits in public. Of these various phenomena, the hijab as a marker symbol has meaning, namely as a form of religious obedience, the identity of a Muslim woman, discipline in public spaces, and camouflage piety. From the perspective of legal pluralism, hijab is an articulation of strictness to the commandments of sharia as well as an inseparable part of the culture that has become a living practice in Indonesian society.